Pengaruh User Interface dan Product Knowledge terhadap Keputusan Pembelian Alat Fitness di Total Fitness Bali yang Dimediasi oleh Meta Business Suite - Soemitro, Bunga Ayu Retno Syafitri; Pratiwi, Nuning Indah; Parasari, Nyoman Sri Manik; Sari, Putu Ratna Juwita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Dengan Meta Business Suite sebagai mediator, ini meneliti bagaimana User Interface dan Product Knowledge mempengaruhi keputusan untuk membeli peralatan kebugaran di Total Fitness Bali. Fokus utama dari penelitian ini adalah kegagalan digital marketing strategies untuk mempengaruhi keputusan pembelian konsumen meskipun platform online semakin populer. The objective of this research is to investigate the ways in which User Interface, Product Knowledge, Meta Business Suite, and purchase decisions are related to each other, both directly and indirectly. Untuk penelitian ini, metode purposive sampling digunakan. 126 responden terlibat dalam interaksi dengan Total Fitness Bali melalui situs web atau platform media sosialnya. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that User Interface has a positive and significant effect on Meta Business Suite and purchase decisions. Product Knowledge significantly influences Meta Business Suite but does not have a direct significant effect on purchase decisions. Meta Business Suite has a significant effect on purchase decisions and successfully mediates the relationship between User Interface and Product Knowledge on purchase decisions. These findings highlight the importance of optimizing digital interface design and content management systems to enhance consumer engagement and support effective digital marketing strategies.